¿QUÉ HAY DETRÁS DE LAS DIFICULTADES QUE PRESENTA LA COMPRENSIÓN DEL CONCEPTO DE NÚMERO REAL? - García O, Gloria; Serrano, Celly; Díaz, Hernán (Tecné, Episteme y Didaxis: TED, 1999)
This article is based upon the concept of epistemological obstacle, error and difficulty An epistemological curriculum and cognitive analysis is carried out, with first semester students, to try to determine the motives for the difficulties in the comprehension of the concept of real number. Using the result of the analysis, suggestions for teaching the concept of real number are made.